Adapting to Incarceration: Inmate Perceptions of Prison Life and Adjustment - Crank, Beverly Reece (2010)
Despite the importance of offenders’ perspectives of the criminal justice system, inmates’ perceptions of prison life remain largely unexplored in correctional research. In the current study, data were analyzed from a survey of approximately 700 incarcerated felons, focusing on their perceptions regarding the perceived difficulty or severity of prison. The correlates of these perceptions were examined, as well as the impact of such perceptions on inmates’ intentions to avoid crime after release. The findings suggest that, while most inmates perceive prison life as difficult, a sizeable proportion of inmates do not find prison time to be overly difficult or severe. Further, inmates who do not view prison as difficult are less likely to report intentions to avoid crime after release. Implications for deterrence theory and future research are discussed